A Efektivitas Layanan Konseling Kelompok Dengan Pendekatan Solution Focused Brief Counseling (SFBC) Dalam Meningkatkan Perilaku Altruistik Siswa - Anida Restiana; Rita Sinthia; Mayang T. Afriwilda (UNIVERSITAS BENGKULU, 2025)
This research aims to test the effectiveness of group counseling services using a solution focused brief counseling (SFBC) approach in increasing students' altruistic behavior. The research method used is quasi-experimental type pre-test post-test control group design. The population in this study was 72 students in classes XI.2 and XI.3. The sample for this research consisted of 10 people who were divided into two groups, namely the experimental group and the control group using purposive sampling techniques. The data collection technique used was an altruistic behavior questionnaire using a Likert scale model. The research data analysis technique uses the t-test (paired sample test). The pre-test and post-test results of the experimental group experienced an increase in the level of altruistic behavior before and after being provided with group counseling services using the solution focused brief counseling (SFBC) approach. This can be seen from the hypothesis results produced in the experimental group which were greater with a t-test value of -32.255 and a significant value of 0.000 < 0.05, while the control group had a t-test value of -3.437 and a significant value of 0.026 < 0.05. This means that there is an influence of group counseling services with a solution focused brief counseling (SFBC) approach which is effective in increasing students' altruistic behavior. This research suggests that guidance and counseling teachers use group counseling services with a solution focused brief counseling (SFBC) approach to increase students' altruistic behavior. Keywords: group counseling, altruistic behavior, solution focused brief counseling.